Transformative learning in the online classroom: A marketing educator’s autoethnographic account - Vergara, Raymond Allan G. (Future Science / FSH-PH Publications, 2023)
This autoethnographic account is a critical reflection on my experience teaching online classes during the pandemic. It is a narrative of my transformation through the 28 months of teaching events marketing courses through the online distance learning modality. I learned that as a marketing educator, my role is to help students develop positive perspectives, attitudes, and behaviors about learning by providing the conditions conducive for a meaningful learning experience. However, as an educator, a student’s learning experience is not my sole responsibility because the learning experience is co-created with the student. My role is an educator is to provide them with opportunities, tools, and knowledge to help them make the most out of their learning experience.